Analisis Penerimaan Tekonologi Internet of Things (IoT) Dalam Pertanian Menggunakan Technology Acceptance Model (TAM) - Basiroh Basiroh; Widya Novita Al Afifah Irwanto (Universitas Muhammadiyah Klaten, 2025)
This The advancement of digital technology has had a significant impact across various sectors, including agriculture. One of the innovations increasingly applied is the Internet of Things (IoT), which enables more effective and efficient monitoring and control of agricultural activities. However, the success of implementing this technology is highly influenced by the level of user acceptance, particularly among farmers. This study aims to analyze the acceptance of IoT in agriculture using the Technology Acceptance Model (TAM), which includes the variables Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention (BI), and Actual Use (AU). The research employed a quantitative approach, with data collected through questionnaires distributed to farmers who are familiar with or have used IoT-based technologies in their agricultural practices. Data analysis was conducted using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The findings reveal that PEOU and PU significantly influence both ATU and BI, which in turn drive the actual use (AU) of IoT technology. Overall, the level of IoT acceptance in agriculture falls into the high category, with respondents’ acceptance percentage exceeding 70%. These results highlight that IoT holds substantial potential to enhance productivity, efficiency, and crop quality. However, its adoption needs to be supported by improved digital literacy, technical assistance, and government policies that facilitate infrastructure development and access to technology